AT SYSTEM FOR EMPLOYEE WORK DISCIPLINE TO INFLUENCE OF LEADERSHIP, SUPERVISION, AND PUNISHMENT AT PT SULTAN AREN INDONESIA - Amelia Rosanti; Rifky Budi Setiawan; Soulthan Saladin Batubara (Jurnal Scientia, 2023)
This research aims to determine and analyze the positive and significant influence of leadership, supervision and punishment on employee work discipline at PT Sultan Aren Indonesia, both partially and simultaneously. This research uses the method quantitative with data analysis techniques used, namely classical assumptions, multiple linear regression, as well as hypotheses. The sample in this study was 57 respondents, using techniques saturated sampling. The research results partially show leadership (X1) has a positive and significant influence on the work discipline (Y) of employees at PT Sultan Aren Indonesia. Supervision (X2) has a positive and significant influence on work discipline (Y) of employees at PT Sultan Aren Indonesia and punishment (X3) has a positive and significant influence on the work discipline (Y) of employees at PT Sultan Aren Indonesia. Meanwhile, the results of simultaneous testing show that leadership (X1), supervision (X2), and punishment (X3) has a positive and significant influence on the work discipline (Y) of employees at PT Sultan Aren Indonesia, with an influence of 74.8%.